Proteomic maps of breast cancer subtypes - Stefka Tyanova (Nature Portfolio, 2016)
Breast cancers have been extensively studied at the genomic and transcriptomic levels in the hope of tailoring therapeutic regimens. Here the authors generate deep coverage proteomes from several clinical breast cancer samples, and use machine learning techniques to uncover biological processes altered in specific cancer subtypes.